KEPADATAN SEL- SEL PENYUSUN BAGIAN FUNDIKA LAMBUNG GARANGAN JAWA (Herpestes javanicus) - , WAHYU PUTRIYANI, drh. Ariana, M.Phil. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The Javan mongoose (Herpestes javanicus) in one of the wildlife animal that belongs to class of mammals and family herpestidae. This animals in the IUCN classified as low risk (least concern) anad CITES classified into appendix III. The Javan mongoose is carnivorous animals, but this animals also eat fruit. This study aims to know cell population of surface epithelial cells, neck mucous cells, zymogenic cells, parietal cells. This study used 3 Javan Mongoose derived from Semarang. The Javan mongoose was euthanased by ketamine HCL followed by perfusion using buffered formalin. Four of gastric were cut 1 cm and fixed by 10% formaldhehide. The tissue was dehydrated and cleared, then embedded in paraffin. The section stained with Hematoxylin - Eosin. The result obtain used preparation photograph under 40 x magnifications and calculated 3 areas from every preparation used opti lab image raster software. The result obtain surface epithelial cell population fundic gland in gastric Javanese small mongoose (Herpestes javanicus) = 594,5 cells/mm2, neck mucous cells = 932 cells/mm2, parietal cells = 452,7 cells/mm2 and zymogenic cells = 1093,2 cells/mm2. The calculation from highest to least is zymogenic cells, neck mucous cells, surface epithelial cells and parietal cells.